Pengaruh Interval Pemberian Dan Dosis Pupuk Organik Cair Terhadap Pertumbuhan Dan Hasil Tanaman Kacang Merah (Phaseolus vulgaris L.) - Mochammad Suud; Yudha Arie Dharma; Ida Sugeng Suyani (Yayasan Perguruan Kampus, 2026)
Population growth and global climate change have increased food demand while reducing agricultural productivity, including that of red kidney bean (Phaseolus vulgaris L.), a commodity that plays an important role in supporting national food security. The decline in red bean production in Indonesia over the past five years has been influenced by extreme climatic conditions and excessive use of chemical fertilizers. Therefore, improvement efforts are needed through the application of liquid organic fertilizer (LOF) with appropriate intervals and dosages. This study aimed to determine the effect of LOF application intervals, LOF dosages, and their interaction on the growth and yield of red kidney bean. The experiment was arranged using a factorial Randomized Complete Block Design (RCBD) with two factors: LOF application interval (I1: once every week, I2: once every two weeks, I3: once every three weeks, I4: once every four weeks) and LOF dosage (D1: 2 ml/L, D2: 3 ml/L, D3: 4 ml/L), each with three replications, resulting in 36 treatment combinations with a total population of 540 plants. The results showed that the LOF application interval had a significant effect on several growth and yield parameters, including number of leaves, number of filled pods per plant, weight of 100 seeds, and yield per hectare. Based on the findings, the I1 treatment produced the best growth and yield. The dosage factor did not significantly affect any parameter, although D1 tended to produce more optimal results. The interaction between interval and dosage showed no significant effect; however, the I1D1 combination exhibited the highest trends in both vegetative and generative performance. Thus, applying LOF at one-week intervals with a dosage of 2 ml/L is recommended as the most effective treatment for improving the growth and yield of red kidney bean.